1999
DOI: 10.1172/jci5347e1
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor a mediates the nongenomic activation of endothelial nitric oxide synthase by estrogen

Abstract: During the production process, the word caspase was misspelled in the title; the correct title appears above. Also, in the legend for Table 1 the mu symbol (µ) was formatted incorrectly; the correct legend appears below. We regret the error. Table 1 Jurkat cells (J16) were preincubated for 2 h with zVAD-fmk (50 µM), DEVD-CHO (100 µM) or left untreated and then exposed to etoposide (10 µg/ml) or IR (30 Gy). After 16 h incubation, Cer content, nuclear fragmentation, mitochondrial transmembrane potential and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
350
4
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(383 citation statements)
references
References 0 publications
21
350
4
8
Order By: Relevance
“…For example, JNK and ERK1/2 pathways are necessary for lipopolysaccharide (LPS)-and interferon-␥-stimulated iNOS expression in mouse macrophage cells, possibly via ␣-tumor necrosis factor secretion, whereas p38 inhibited induction [31]. The induction of endothelial NOS (eNOS, NOS-3) by estrogen, fibroblast growth factor or epidermal growth factor in endothelial cells involves the Ras-ERK pathway [38,233]. eNOS is phosphorylated, and thus activated, by the serine/threonine protein kinase AKT, which is recruited to the cell membrane by PI3-kinase as an antiapoptotic mechanism in the response of endothelial cells to shear stress [54].…”
Section: Nitric Oxide and Mapk Signalingmentioning
confidence: 99%
“…For example, JNK and ERK1/2 pathways are necessary for lipopolysaccharide (LPS)-and interferon-␥-stimulated iNOS expression in mouse macrophage cells, possibly via ␣-tumor necrosis factor secretion, whereas p38 inhibited induction [31]. The induction of endothelial NOS (eNOS, NOS-3) by estrogen, fibroblast growth factor or epidermal growth factor in endothelial cells involves the Ras-ERK pathway [38,233]. eNOS is phosphorylated, and thus activated, by the serine/threonine protein kinase AKT, which is recruited to the cell membrane by PI3-kinase as an antiapoptotic mechanism in the response of endothelial cells to shear stress [54].…”
Section: Nitric Oxide and Mapk Signalingmentioning
confidence: 99%
“…For example, osteocyte apoptosis and bone loss is prevented by the androgen and estrogen steroid receptors through nontranscriptional activation of protein kinase Src and mitogen-activated protein kinase [65,66]. Vascular nitric oxide production and vasodilation by estrogen depends on nontranscriptional activation of eNOS and are mediated by ERα-dependent activation of the PI3 K/Akt pathway [67,68,69]. Indeed, the vascular protective effects of estrogen are dependent on the nontranscriptional activation of eNOS via PI3 K/Akt [68].…”
Section: Rapid Nontranscriptional Effects Of Grmentioning
confidence: 99%
“…Some investigators have been able to demonstrate (38) increased expression of endothelial nitric oxide synthase in women treated with estrogens. The effects of estrogens on nitric oxide synthesis is believed to be manifested by rapid non-genomic (without changes in gene expression) effects (38,39). Elucidation of this phenomenon has indicated that the non-genomic effects may still be modulated by estrogen receptors and the readers are referred to an excellent review of this topic by Mendelsohn and Karas (39).…”
Section: Estrogen and Vascular Tonementioning
confidence: 99%